2019
DOI: 10.1007/s10237-019-01269-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of morphological and hemodynamical indexes in abdominal aortic aneurysms as preliminary indicators of intraluminal thrombus deposition

Abstract: In this paper we study the correlation between the Wall Shear Stress (WSS), a haemodynamical index derived from numerical simulations, and an new index MFA-ILT for the characterisation of intraluminal thrombus (ILT) in presence of abdominal aortic aneurysms. Based on the processing of medical images, we define our index MFA-ILT by projecting onto lumen surface a measure of the ILT thickness. From the physical point of view, haemodynamical indexes describe the mechanical stimuli at which the luminal surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Previous studies had originally hypothesized that high values of OSI, which indicated a highly disturbed flow near wall, were related to the accumulation of thrombus 10 . Other studies have challenged this by showing that low OSI values could be an indicative of a persistent flow circulatory pattern, which could explain the no correlation reported among these parameters 7 . Our results, by identifying high and low OSI levels over regions where changes in ILT were observed agree with both mechanisms; which could explain the lack of correlation determined by our and other recent investigations.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies had originally hypothesized that high values of OSI, which indicated a highly disturbed flow near wall, were related to the accumulation of thrombus 10 . Other studies have challenged this by showing that low OSI values could be an indicative of a persistent flow circulatory pattern, which could explain the no correlation reported among these parameters 7 . Our results, by identifying high and low OSI levels over regions where changes in ILT were observed agree with both mechanisms; which could explain the lack of correlation determined by our and other recent investigations.…”
Section: Discussionmentioning
confidence: 98%
“…In case of AAAs, low TAWSS values have also being associated to the formation of thrombus 9 . Specifically, the observation of low levels of TAWSS in regions where thrombus accumulation is high has led to the suggestion for a potential correlation among these two 7,21 . Biochemically, low values of WSS are related to a decrease in the production of prostacyclin, prostaglandins, 22 and nitric oxide (NO), 23 which are agents in charge of signaling multiple biological functions (e.g., vasodilation, remodeling; among others) and protecting the arterial wall against pro‐thrombotic activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of abdominal aortic aneurysms, although a different disease, aneurysm morphology and hemodynamics have been linked to intraluminal thrombus formation which has been identified as one of the drivers of aortic aneurysm progression. 20,21 Furthermore, hemodynamic and morphological factors, in combination with clinical data and shape of the intra-luminal thrombus, have been proposed as predictors of aortic aneurysm growth using data from longitudinally followed abdominal aortic aneurysms. 22 In contrast, intra-aneurysmal thrombus is rare in cerebral aneurysms and it mostly observed in large or giant aneurysms (>25 mm), and the mechanisms for their evolution remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodynamics is indeed known to be related to abdominal aortic aneurysm (AAA) development, intraluminal thrombus deposition, and finally expansion till rupture. 2 Wall shear stresses (WSS) and blood pressure are confirmed to be major hemodynamic determinants of this expansion and rupture. Moreover, also the aortic blood impingement against the inner lumen could explain different rates of growth of AAA.…”
mentioning
confidence: 99%